A study on the impact of social media on travellers’ attitudes towards purchase decisions in tourism industry with reference to Karnataka - Mr. SHIVAKUMAR C, Dr. SIVAKUMAR V (South Eastern European Journal of Public Health, 2025)
The use of social media on traveller has become widespread. It has altered the ways in which we interact with one another use available information and make purchases. The travel and tourism industry has also undergone a significant transformation in the past decade due to the emergence of social media. These statistics illustrate the notable impact of social media on prospective travellers, its influential role in the travel industry, and its potential for promoting diverse destinations. This quantitative study employed the descriptive research design, to describe social media posts’ characteristics and impact on travel decisions and preferences. Purposive sampling under the non-probability sampling methods was also used. This study aimed to bridge this gap, and additionally aimed for its findings to contribute to tourism establishments’ and stakeholders’ knowledge of social media as a tool for promotion and reaching out to a wider range of tourists and an attempt to determine the role played by social media platforms in promoting sustainable tourism in the states of Karnataka.